Manajemen Komunikasi antara Pengasuh Pondok Pesantren dengan Orang Tua Santri dalam Pendidikan Anak - Salsabila Aufa Khairunnisa (Jurnal Pendidikan Nusantara, 2023)
Education is a process of forming human character through learning media. The progress of a nation can be seen from the quality of its education. When a nation or country is advanced, it can be said that the education of that nation or country has very good quality. Because education also has an important role in life. Nowadays, it is very important to instill religious education in children because the rapid development of technology makes some parents unable to supervise their children always in using technology. Therefore, it is very necessary to instill Islamic education in life. The research method used was an interview with one of the leaders of the Darul Madinah Islamic boarding school and analyzing journals. One of the applications in instilling Islamic education in children is by putting children in Islamic boarding schools. There are two types of Islamic boarding schools today, namely modern Islamic boarding schools and traditional Islamic boarding schools. Modern Islamic boarding schools are usually very neat in their management and administration and the implementation of education is balanced between formal education and religious education. In this study, the author uses the object of the Darul Madinah Madiun Islamic Boarding School because the modern boarding school and the communication management system with the parents of the students are very clear and organized. So that it is easier for the parents of the students to monitor the development of their children's education properly, because the one who accompanies the students for 24 hours is the caregiver and not the parents of the students themselves. The Darul Madinah Madiun Islamic Boarding School has several strategies that are applied in communicating with the parents of the students. One of them is by using current technology that exists